Understanding the effects of ultrasound processng on texture and rheological properties of food. Issue 6 (15th December 2021) - Aslam, Raouf; Alam, Mohammed Shafiq; Kaur, Jaspreet; Panayampadan, Afthab Saeed; Dar, Owias Iqbal; Kothakota, Anjineyulu; Pandiselvam, Ravi
Abstract: The demand for the production of high quality and safe food products has been ever increasing. Consequently, the industry is looking for novel technologies in food processing operations that are cost‐effective, rapid and have a better efficiency over traditional methods. Ultrasound is well‐known technology to enhance the rate of heat and mass transfer providing a high end‐product quality, at just a fraction of time and energy normally required for conventional methods. The irradiation of foods with ultrasound creates acoustic cavitation that has been used to cause desirable changes in the treated products. The technology is being successfully used in various unit operations such as sterilization, pasteurization, extraction, drying, emulsification, degassing, enhancing oxidation, thawing, freezing and crystallization, brining, pickling, foaming and rehydration, and so forth. However, the high pressure and temperature associated with the cavitation process is expected to induce some changes in the textural and rheological properties of foods which form an important aspect of product quality in terms of consumer acceptability. The present review is aimed to focus on the effects of ultrasound processing on the textural and rheological properties of food products and how these properties are influenced by the process variables. Abstract : Effects of ultrasound processing on the textural and rheological properties of food.